Effects of steam-flaked sorghum grain or corn and supplemental fat on feedlot performance, carcass traits, longissimus composition, and sensory properties of steers - Brandt, Robert T., Jr.; Kuhl, Gerry L.; Campbell, R.E.; Kastner, Curtis L.; Stroda, Sally L. (American Society of Animal Science, 2008)
One hundred forty British x Exotic crossbred, yearling steers (370 kg) were used in a 2 x 2 factorial experiment to evaluate main effects and the interaction of grain type (steam-flaked sorghum grain [SFSGI or steam-flaked corn [SFCI) and level of supplemental fat (0 or 4% yellow grease WGll on feedlot performance, diet NE concentration, carcass traits, and chemical composition and sensory properties of longissimus muscle. Steer performance and estimated dietary NE, and NE, values were not different between SFSG and SFC. Supplemental YG improved CP 5 .05) gain/feed and estimated NE, and NE, of both SFSG and SFC diets. Compared with steers fed SFSG, steers fed SFC had a more yellow (P c .05) subcutaneous fat color. Supplemental YG had an additive effect (P c .025) on yellow color of subcutaneous fat but improved (P c .08) the lean color of longissimus muscle. Grain type or supplemental YG had no effect on sensory properties or mechanical shear of longissimus muscle. Longissimus muscle cholesterol content was elevated (P c .05) by supplemental YG (.49 vs .52 mg/g of wet tissue for 0 vs 4% YG, respectively); however, the biological significance of this result is question ,- ble. Similarly, effects of YG on increased (P c .05) stearic acid concentration and a higher concentration (P c .051 of linoleic acid measured in longissimus muscle of steers fed SFSG vs SFC were small in magnitude. These data indicate that under the conditions of this experiment, NE contents of SFSG and SFC were similar. Beef produced from sorghum grain is similar in quality and sensory properties to that produced from corn. There was no correlation (r = -.001) between degree of marbling and tissue cholesterol content, suggesting that for closely trimmed beef cuts, selection for higher quality by consumers will not elevate cholesterol intake.
Keywords: Food science; Steers; Sorghum grain; Corn; Feedlots; Fats; Palatability